(3SaQ GdSYGOIs - (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s ((3CHh HcQ Hf efLc s)
(3ChdgG (B:s
(3HYO GdMeO hGdKfGA Ydi MVQI Pi GdcHQjGA afJYde WGFaI GdCMHGH hGdCUMGH Cf WQjb GdMb GdPi gh GdUQGW GdeSJbje aiEKHGJ CHhGH KHJJ ai UMjM GdCNHGQ s
(3BNQgG (B:s
(3hHGH EaJQGb GdCeI Edi EKfjf hSHYjf aQbg de jKHJ ajg TF hGddg CYde HGdUhGH hGdMeO ddg QH GdYGdejf Je gPG GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bhHdJ HCUdgG GdebQhAI Ydi GdTjN HQgGf GdOjf GdfGLi s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs